Взаємодії населення степу та лісостепу України за доби пізньої бронзи - Гершкович, Я.П. (Археологія, 2003)
У статті розглянуто питання послідовності та наслідків взаємодій населення степової та лісостепової зони України з середини до останньої чверті II тис. до Р. X. В статье рассматривается динамика взаимодействия срубной и сабатиновской культур эпохи поздней бронзы и их влияние на тшинецкую культуру. Учитывается вхождение каждой из них в отдельные культурно-исторические общности: Ноа — Сабатиновка — Кослоджень (НСК), тшинецко-комаровскую (ТК), срубную (СКИО). Выясняется общая синхронность финалов этих образований, наступивших не позднее периодов НаА1/НаА2 (ХП/Х1 вв. до н. э.). Как контакты со срубной культурой не были причиной исчезновения сабатиновской, так и исчезновение тшинецкой культуры не связано с ее контактами с восточными и юго-восточными соседями. Вероятно, причину следует искать в разрушении, не без влияния извне, предшествовавших продолжительных связей между ними, что привело к исчезновению налаженной системы обмена в разных сферах производства, его технологического и, возможно, сырьевого обеспечения. Именно в этих условиях завершилось функционирование лобойковского очага металлообработки и вследствие появления новых участников исторических процессов в Причерноморье и Поднепровье сформировался кардашинский очаг, ареал которого удивительным образом соответствует зоне бывших непосредственных контактов НСК со СКИО и последней с ТК. The article deals with dynamic of interaction of Zrubna and Sabatynivs’ka cultures of the Late Bronze epoch and their influence on Tshinets’ka culture. It is taken into account that each of them forms a part of the separate cultural-historical community that is Noa-Sabatynivka-Koslodzhen’ (NSK), Tshinets’ko-Komarivs’ka community (TK), Zrubna cultural-historical community (ZCHC). It is elucidated the finales of these formations were synchronous as a whole and came not later then periods of HaAl/HaA2 (the 12th or 11th century BC). The same way as the relations with Zrubna culture weren’t the reason of vanishing Sabatynivs’ka one and vice versa, so, interrelations of Tshinets’ka culture with these its eastern and southeastern neighbours weren’t the reason of its vanishing. Probably, the reason should be looked for in disconnecting presiding continuing links between them but not without outside influence. This disconnecting entailed vanishing useful system of exchange in different spheres of craft, its technology and perhaps source of raw materials. Namely under these conditions the functioning Loboykibs’kyj center of metalwork came to an end, and Kardashs’kyj center came into being at the expense of new subjects of historical processes on the territory to the north from the northern coast of the Black Sea and in the area of Dnieper-river, the area of which wonderfully met the zone of former immediate contacts between NSK. and ZCHC and between the last one and TK.